Evaluation of the pharmacokinetic interactions of montmorillonite powder or loperamide on pyrotinib in healthy volunteers - Wang, Yike; Li, Dai; Zhang, Tong; Xu, Sumei; Zhang, Yanxin; Zhao, Kaijing; Li, Shaorong; Shen, Kai; Li, Xiaomin; Xu, Pingsheng (Frontiers in Pharmacology, 2025)
AimsTo investigate the potential pharmacokinetic interactions of montmorillonite powder or loperamide on pyrotinib.MethodsThis study was a single-center, open-label, single-dose, fixed-sequence clinical trial conducted with healthy volunteers. The participants were divided into two groups (A and B), each consisting of 18 subjects. Both groups received a single oral dose of 400 mg of pyrotinib on day 1. On day 9, Group A received a single dose of 400 mg of pyrotinib followed by 3 g of montmorillonite powder 2 h later, while Group B received a single dose of pyrotinib and 4 mg of loperamide after breakfast on day 9, followed by single oral doses of 2 mg of loperamide at 2 and 4 h post-administration. Blood samples were collected to determine pyrotinib blood concentrations.ResultsIn Group A, the combination treatment with montmorillonite powder resulted in a decrease in Cmax, AUC0-t, and AUC0-∞ by 26.7%, 33.1%, and 32.4%, respectively, compared to pyrotinib alone. In Group B, the combination treatment with loperamide had minimal impact on pyrotinib’s absorption rate but slightly increased AUC0-t and AUC0-∞ by approximately 18% and 19%, respectively, while decreasing CL/F and prolonging the t1/2.ConclusionEven when montmorillonite powder was administered 2 h after pyrotinib dosing, it still reduced systemic exposure of pyrotinib by 32.4% in AUC0-∞. In contrast, loperamide increased pyrotinib exposure by 19% in AUC0-∞ when used together. Based on these findings, loperamide is recommended for symptom control, while montmorillonite powder should not be co-administered with pyrotinib or any drug requiring optimal absorption.Clinical trial registration[ClinicalTrials.gov], identifier [NCT05252546].